Komunikasi Sosial bagi Kepolisian melalui Media Video Instruksional - Dewi Kartika Sari; Sampoerno Sampoerno; Seto Herwandito; Budhi Widi Astuti; Ester Krisnawati; Pratiwi Cristin Harnita; Sih Natalia Sukmi; Bonardo Marulitua Aritonang (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2020)
Social communication in the police institution is important to develop community-oriented policing (COP). This social communication can be a communication bridge between the police and the community for the purpose of integration or social adaptation. For this purpose, community service is carried out at the Pusdik Binmas Lemdiklat Polri in the form of making instructional videos for Binmas functions in the community. Instructional videos are expected to provide an overview about the synergy between the police and the community. The method used in this service is carried out through pre-production, production and post-production activities. As a result of community service there are eight instructional videos for use at the Pusdik Binmas Lemdiklat Polri.